(untitled) (Boletín Micológico, 2004)
This paper can be considered as a little constribution to knowledge of fungal biodiversity in Namibia. Soils, seed dung and some vegetal substrata such as herb, leaves and bark were collected at random in order to investigate the presence of tropical microfungi and to determine the significance of some fungal taxa in the Namibian ecosystem. A total of 49 genera and 80 taxa predominantly anamorph of Ascomycota was recordered, most of them (51%) were isolated from soil and many were considered common tropical microfungi. The most representative isolate taxa in all substrata analized or in some of them were: Alternaria, Aspergillus, Aureobasidium, Bipolaris, Chaetomium, Fusarium, Penicillium, and Phoma. It is interesting to note in vegetables the presence of Lasiobolidium spirale, quite a rare species.